Post i zapobieganie jego ewentualnym skutkom zdrowotnym w świetle korespondencji św. Hieronima - Kołosowski, Tadeusz (Saeculum Christianum. Pismo Historyczne, 2020)
In this article the author deals with the issue of health care, which Jerome addresses in his letters to ascetics who, in many cases, by their extreme approach to the practice of fasting, destroy their health. On the one hand, Jerome teaches them how to understand and practice fasting in the Christian sense, and on the other hand, similar to today's dietitians, he tries to suggest a proper diet in such a way that it is possible to practice Christian fasting and lead one's life in accordance with the monastic vocation, while maintaining both spiritual and bodily health.